A Case of Adalimumab-Induced Pneumonitis in a 45-Year-Old Man with Crohn's Disease. Issue 5 (2011) - Reid, James D; Bressler, Brian; English, John
Abstract : Adalimumab is a human monoclonal antibody against tumour necrosis factor-alpha that has been associated with acute lung toxicity, mainly in patients with rheumatoid arthritis. Descriptions of similar patterns of lung injury in patients treated with adalimumab for inflammatory bowel disease are emerging in the literature. A case involving a 45-year-old man with Crohn's disease who developed a nonbronchiolitis inflammatory nodular pattern of lung injury after starting adalimumab is reported.